y(12x+16z)=x(12y+14z)

Simple and best practice solution for y(12x+16z)=x(12y+14z) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for y(12x+16z)=x(12y+14z) equation:


Simplifying
y(12x + 16z) = x(12y + 14z)
(12x * y + 16z * y) = x(12y + 14z)
(12xy + 16yz) = x(12y + 14z)
12xy + 16yz = (12y * x + 14z * x)
12xy + 16yz = (12xy + 14xz)

Add '-12xy' to each side of the equation.
12xy + -12xy + 16yz = 12xy + -12xy + 14xz

Combine like terms: 12xy + -12xy = 0
0 + 16yz = 12xy + -12xy + 14xz
16yz = 12xy + -12xy + 14xz

Combine like terms: 12xy + -12xy = 0
16yz = 0 + 14xz
16yz = 14xz

Solving
16yz = 14xz

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Divide each side by '16z'.
y = 0.875x

Simplifying
y = 0.875x

See similar equations:

| 28x^2-164x=24 | | 17x-8=-25 | | -3(1-h)=-6-6n | | -1t-23=-15 | | X+5+7=11 | | -6=-24x-15 | | f(x)=ln(121sin^2x) | | y(12x+16z)=z(14x+16y) | | 2x+8x=80 | | 9y-15=-45+4y | | -2(x-8)-23=-7 | | x(12y+14z)=z(14x+16y) | | 23-x=47 | | z(14x+16y)=y(12x+16z) | | 8n-11=13+2n | | 3X^2-3X-XY+Y= | | 15+3=1513 | | x(12y+14z)=y(12x+16z) | | 7x-2=-13 | | 3(4x-7)=4x-25 | | x(12y+14z)=y(12x+16y) | | x^2+5x=110+4x | | 2(3+4x)-2=28 | | 30n^2-192=216n | | y(8x+8z)=z(10x+8y) | | x(8y+10z)=y(8x+8z) | | x(8y+10z)=y(8x+8z)andy(8x+8z) | | 3x^2-5x+6=2x^2+4x-14 | | 4=7+1+6x | | m+qn=r | | 5x^2-20x+6=0 | | 2m+p=16 |

Equations solver categories